Characteristics and Visual Outcomes of Eye Trauma in the Chinese Armed Services. Issue 4 (1st December 2012) - Xiao, J; Zhang, Maonian; Jiang, C; Zhang, Y; Qiu, H; Chaloulias, C; Suleman, H
Abstract : Objectives: To outline the characteristics and outcomes of eye injuries in the Chinese People's Liberation Army. Methods: A retrospective review of military inpatient eye injuries, in one military region, population 250, 000 soldiers, between January 2006 and December 2010. Results: There were 709 eye injury patients (759 eyes) during the 5-year period with an incidence of inpatient eye injuries of 57 per 100, 000 person-years. The mean age of patients was 24 years, the vast majority male. The majority of eye injuries occurred during recreational time (62%), with the commonest causing being violence (46%). The immediate post-injury vision acuity of 48% of eyes was >6/12; 93% of cases had mechanical ocular injuries and 7% had non-mechanical ocular injuries. 71% of patients were sent to an evacuation hospital within 24 hours and 75% had surgery within 24 hours of injury. The majority of cases (97%) were hospitalized for one visit. On discharge, there was a statistically significant improvement in visual outcomes with 85% of eyes achieving >6/12. Conclusions: Eye injuries secondary to violence were a frequent occurrence amongst young male PLA members, particularly during recreational time. Most injuries were not sight-threatening, with the majority of patients achieving an excellent visual outcome.